Forecasting the Development of Different Solar Cell Technologies - Arturo Morales-Acevedo; Gaspar Casados-Cruz (International Journal of Photoenergy)
Solar cells are made of several materials and device structures with the main goal of having maximum efficiency at low cost. Some types of solar cells have shown a rapid efficiency progress whereas others seem to remain constant as a consequence of different factors such as the technological and economic ones. Using information published by the National Renewable Energy Laboratory (NREL) about the increase of solar cells record efficiency, we apply a simple mathematical model to estimate the evolution in the near future for the different cell technologies. Here, as an example, we use data for solar cells made with representative materials and structures of each of the three “PV generations.”